2021
DOI: 10.1101/2021.10.28.21265436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated analysis of patient networks and plasmid genomes reveals a regional, multi-species outbreak of carbapenemase-producing Enterobacterales carrying bothblaIMPandmcr-9genes

Abstract: The incidence of carbapenemase-producing Enterobacterales (CPE) is rising globally, yet Imipenemase (IMP) carbapenemases remain relatively rare. This study describes an investigation of the emergence of IMP-encoding CPE amongst diverse Enterobacterales species between 2016 and 2019 in patients across a London regional hospital network.A network analysis approach to patient pathways, using routinely collected electronic health records, identified previously unrecognised contacts between patients who were IMP CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…To study this emergence, we demonstrated that bla IMP-4 IncHI2A plasmids were highly similar to non- bla IMP-4 IncHI2A plasmids in E. hormaechei ST93, ST114 and ST190 that may have served as acceptors for the bla IMP-4 integron. In addition, there was possible importation from outside sources: bla IMP-4 has been found in both IncHI2A and IncL/M plasmids in Australian isolates 2, 4, 9, 26 and bla IMP-4 -harbouring IncHI2A plasmids are emerging as a global issue, having been noted in a recent multi-hospital outbreak in the United Kingdom 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study this emergence, we demonstrated that bla IMP-4 IncHI2A plasmids were highly similar to non- bla IMP-4 IncHI2A plasmids in E. hormaechei ST93, ST114 and ST190 that may have served as acceptors for the bla IMP-4 integron. In addition, there was possible importation from outside sources: bla IMP-4 has been found in both IncHI2A and IncL/M plasmids in Australian isolates 2, 4, 9, 26 and bla IMP-4 -harbouring IncHI2A plasmids are emerging as a global issue, having been noted in a recent multi-hospital outbreak in the United Kingdom 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pathogen factors, we were able to analyse patient factors. While genomic surveillance previously focused on lineage-level analysis, long-read sequencing technologies have improved analysis of plasmids and other mobile genetic elements 12, 27, 33 . In our study, these insights proved informative both for understanding within-patient and between-patient bla IMP-4 spread.…”
Section: Discussionmentioning
confidence: 99%